STRATEGI PEMBELAJARAN BAHASA ARAB YANG EFEKTIF UNTUK PEMULA - Ardiansyah Siregar, Febry; Kamalia (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Based on this background, this study aims to identify and examine effective Arabic language learning strategies for beginners, so that they can serve as a reference for educators, educational institutions, and independent learners in improving the quality of learning. This research methodology uses a qualitative approach with descriptive methods. This study aims to describe in depth Arabic language learning strategies that are considered effective for beginners. The main data sources were obtained through in-depth interviews with Arabic language teachers, observations of classroom learning activities, and documentation of teaching materials and lesson plans. The data collection technique was carried out using triangulation, namely a combination of observation, interviews, and documentation to obtain more valid and comprehensive data. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. Arabic language learning for beginners is most effective when starting from the foundation of sound and writing (hijaiyah letters and harakat), then immediately directed to the use of language in real contexts. The combination of the Communicative Approach, thematic vocabulary reinforcement (tamyīz), and istimā‘ (listening) and kalām (speaking) exercises creates a natural learning flow: listen → speak → read/write → use in everyday situations. Visual/audiovisual media, educational games, role-play, creative projects, and technology support (apps, videos, online quizzes) maintain engagement and bridge the gap between the classroom and real life.